Gluten Causes Gastrointestinal Symptoms in Subjects Without Celiac Disease: A Double-Blind Randomized Placebo-Controlled Trial - Biesiekierski, Jessica R; Newnham, Evan D; Irving, Peter M; Barrett, Jacqueline S; Haines, Melissa; Doecke, James D; Shepherd, Susan J; Muir, Jane G; Gibson, Peter R (The American journal of gastroenterology, 2011)
Despite increased prescription of a gluten-free diet for gastrointestinal symptoms in individuals who do not have celiac disease, there is minimal evidence that suggests that gluten is a trigger. The aims of this study were to determine whether gluten ingestion can induce symptoms in non-celiac individuals and to examine the mechanism. A double-blind, randomized, placebo-controlled rechallenge trial was undertaken in patients with irritable bowel syndrome in whom celiac disease was excluded and who were symptomatically controlled on a gluten-free diet. Participants received either gluten or placebo in the form of two bread slices plus one muffin per day with a gluten-free diet for up to 6 weeks. Symptoms were evaluated using a visual analog scale and markers of intestinal inflammation, injury, and immune activation were monitored. A total of 34 patients (aged 29-59 years, 4 men) completed the study as per protocol. Overall, 56% had human leukocyte antigen (HLA)-DQ2 and/or HLA-DQ8. Adherence to diet and supplements was very high. Of 19 patients (68%) in the gluten group, 13 reported that symptoms were not adequately controlled compared with 6 of 15 (40%) on placebo (P=0.0001; generalized estimating equation). On a visual analog scale, patients were significantly worse with gluten within 1 week for overall symptoms (P=0.047), pain (P=0.016), bloating (P=0.031), satisfaction with stool consistency (P=0.024), and tiredness (P=0.001). Anti-gliadin antibodies were not induced. There were no significant changes in fecal lactoferrin, levels of celiac antibodies, highly sensitive C-reactive protein, or intestinal permeability. There were no differences in any end point in individuals with or without DQ2/DQ8. "Non-celiac gluten intolerance" may exist, but no clues to the mechanism were elucidated.